Comparative Study of Qualitative and Quantitative Analyses of Contrast-Enhanced Ultrasound and the Diagnostic Value of B-Mode and Color Doppler for Common Benign Tumors in the Parotid Gland - Yan, Meiying; Xu, Dong; Chen, Liyu; Zhou, Lingyan (Frontiers in Oncology, 2021)
Purpose: To preliminarily identify 3 common benign parotid gland tumors: pleomorphic adenomas (PA), Warthin tumors (WT), and basal cell adenomas (BCA) by qualitative and quantitative analyses using contrast-enhanced ultrasound (CEUS). Methods: Preoperative images of parotid gland masses were analyzed, including 129 cases of ultrasonography (US) and color Doppler sonography (CDS) and 110 cases of qualitative and quantitative CEUS. The diagnosis was confirmed by postsurgical pathology outcomes. Results: PA presented low and heterogeneous enhancement and echo-free area while most WT and BCA presented with high and relatively homogeneous enhancement. Compared with WT and BCA groups, a “slow in” pattern was more common in the PA group and a “slow out” pattern was more frequently noted in the WT group than in the PA and BCA groups. The unique features of qualitative CEUS in the PA group enable distinguishing PA from the 2 other groups. The further distinction among the groups was made based on quantitative parameters of time-intensity curves (TICs), which revealed that the mean peak intensity (PI), mean transit time (MTT), the area under the curve (AUC), and time from peak to one half (HT) exhibited significant differences. ROC analysis was next applied to determine the optimal cutoff points to predict the diagnostic tendency among the groups. When the rising slope (RS) was >2.145, the possibility of BCA was greater than WT. Conclusions: CEUS ultrasound is of significant value in the differential diagnosis of the 3 common benign parotid gland masses.